Identification of Contaminants in the Upper Basin of the Santa River: Implications for the Ecosystem - Cruz - Reyes , Fray Masias; Comeca - Chuquipul, Miguel; Aronés - Cisneros , Angel; Chacon - Gonzales, Roselyn; Cruz - Ledesma, Sigrid; Comeca - Ramirez, Nolberto (Journal of Ecohumanism, 2025)
The study aimed to identify the main pollutants in the upper basin of the Santa (Ancash – Perú) River and evaluate their relationship with mining tailings and other sources of contamination. Physical-chemical, inorganic, microbiological and parasitological parameters were analyzed at eight sampling points between the Negro River and Catac, using data from the National Water Authority (ANA) and comparing with the Environmental Quality Standards (ECA). The results revealed high levels of iron and aluminum at point 1, arsenic and chlorides at point 2, and bacteria such as Coliforms and E. coli at points 2 and 4, which implies a risk to public health and the ecosystem. It is concluded that constant monitoring and remediation measures are necessary in critical areas to protect water quality.